2018
DOI: 10.5935/1518-0557.20180041
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a time-lapse model; a retrospective study comparing embryo evaluation using a morphokinetic model to standard morphology with live birth as endpoint

Abstract: ObjectiveTo validate a morphokinetic implantation model developed for EmbryoScope on embryos with known outcome, compared to standard morphology in a retrospective single center study.MethodsMorphokinetic annotation of 768 embryos with known outcome between 2013 -2015; corresponding to 116 D3 fresh embryos, 80 D6 frozen blastocysts, and 572 D5 blastocysts, fresh or frozen. The embryos were ranked by the KIDScore into five classes, KID1-5, and grouped into four classes based on standard morphology. Pregnancy ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
(46 reference statements)
1
21
1
Order By: Relevance
“…Several authors have indicated that morphokinetic parameters are characteristic of blastocyst formation (Wong et al , 2010; Conaghan et al , 2013; Milewski et al , 2015; Motato et al , 2016) and pregnancy or implantation (Meseguer et al , 2011; VerMilyea et al , 2014; Basile et al , 2015; Liu et al , 2016; Milewski et al , 2016; Motato et al , 2016; Petersen et al , 2016; Carrasco et al , 2017) but the general applicability of former morphokinetic algorithms for pregnancy, implantation or birth prediction is currently subject to controversy. Some authors who were not involved in developing the algorithms have maintained that time-lapse algorithms have a significantly higher predictive power than conventional scoring (Adamson, 2016; Kieslinger et al , 2016; Adolfsson et al , 2018; Liu et al , 2018), while other authors were unable to show a significant predictive capability for pregnancy, implantation or live birth (Kirkegaard et al , 2014; Yalçınkaya et al , 2014; Fréour et al , 2015; Ahlstrom et al , 2016; Goodman et al , 2016; Barrie et al , 2017; Adolfsson et al , 2018). These discrepancies are probably due to the fact that timing is markedly influenced by the fertilisation method (Lemmen et al , 2008), culture medium (Ciray et al , 2012), oxygen level (Kirkegaard et al , 2013a), population features (Fréour et al , 2013; Wissing et al , 2014) and controlled stimulation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have indicated that morphokinetic parameters are characteristic of blastocyst formation (Wong et al , 2010; Conaghan et al , 2013; Milewski et al , 2015; Motato et al , 2016) and pregnancy or implantation (Meseguer et al , 2011; VerMilyea et al , 2014; Basile et al , 2015; Liu et al , 2016; Milewski et al , 2016; Motato et al , 2016; Petersen et al , 2016; Carrasco et al , 2017) but the general applicability of former morphokinetic algorithms for pregnancy, implantation or birth prediction is currently subject to controversy. Some authors who were not involved in developing the algorithms have maintained that time-lapse algorithms have a significantly higher predictive power than conventional scoring (Adamson, 2016; Kieslinger et al , 2016; Adolfsson et al , 2018; Liu et al , 2018), while other authors were unable to show a significant predictive capability for pregnancy, implantation or live birth (Kirkegaard et al , 2014; Yalçınkaya et al , 2014; Fréour et al , 2015; Ahlstrom et al , 2016; Goodman et al , 2016; Barrie et al , 2017; Adolfsson et al , 2018). These discrepancies are probably due to the fact that timing is markedly influenced by the fertilisation method (Lemmen et al , 2008), culture medium (Ciray et al , 2012), oxygen level (Kirkegaard et al , 2013a), population features (Fréour et al , 2013; Wissing et al , 2014) and controlled stimulation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing pregnancy rate was relatively high (57.2% vs. 60.1%, p = 0.71). Recently, the predictive value of morphokinetic parameters has been studied 13,26,[38][39][40][41][42] . Our study was a retrospective cohort study which was compiled data from July 2014 to July 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos are ranked in five groups predicting their ability to develop into a blastocyst with an area under the curve (AUC) of 0.75 and implantation potential with an AUC of 0.65 (indicative of intermediate prediction) [12]. Interestingly, a recent study showed that the KIDScore was superior regarding predicting implantation and ongoing pregnancy rates when compared to only scoring embryo morphology [13].…”
Section: Introductionmentioning
confidence: 99%